Sex-specific physiological responses of recovering F2 individuals following parental (F1) exposure to the isolated and combined effect of hypoxia and marine heatwave events in the marine calanoid copepod Acartia tonsa - Fanny Vermandele; Ellia Roy; Matthew Sasaki; Gesche Winkler; Hans G Dam; Piero Calosi; Diana Madeira (PANGAEA, 2025)
Specimens (F1) of the marine calanoid copepod Acartia tonsa were exposed for five days under laboratory conditions to the isolated or combined effects of hypoxia and a marine heatwave. Then, their offspring (F2) were returned to control conditions (C: 18 °C, 100 % O? sat.) for the rest of their life cycle to simulate a recovery period. This dataset compiles all morphological and physiological measurements, namely routine metabolic oxygen consumption rates (μmol h?^1 and μmol mg?^1 h?^1), upper thermal limit (°C) as well as length (mm) and dry weight (μg) of recovering F2 adults following parental exposure to the isolated and combined effects of hypoxia and a marine heatwave.
In: Vermandele, F et al. (2025): Survival and sex-specific physiological responses of the marine copepod Acartia tonsa following parental exposure to the combined effects of hypoxia and a marine heatwave [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973404